New eutherian mammals from the Late Cretaceous of Aix‐en‐Provence Basin, south‐eastern France. (29th October 2013) - Tabuce, Rodolphe; Tortosa, Thierry; Vianey‐Liaud, Monique; Garcia, Géraldine; Lebrun, Renaud; Godefroit, Pascal; Dutour, Yves; Berton, Sévérine; Valentin, Xavier; Cheylan, Gilles
Abstract : In Europe, the fossil record of Late Cretaceous eutherian mammals is very poor, being limited to only three genera ( Labes, Lainodon, and Valentinella ). Labes and Lainodon are well‐supported members of Zhelestidae, a stem eutherian clade, whereas Valentinella is more problematic, being recently considered as a nomen dubium . Based on X‐ray computed microtomography scan analysis of the holotype and thanks to the discovery of new specimens from the type locality (Vitrolles‐La Plaine, south‐eastern France, late Maastrichtian), we reassessed Valentinella . This genus is unique by the association of an enlarged and rounded jaw angle with an assumed relatively elevated angular process, a bulbous protoconid and an unbasined heel on p4, a p5 with a wide molariform talonid and a hypoflexid, a robust molar morphology with a potential specialized crushing‐grinding function (bulbously constructed cusps, large talonid, and horizontal apical wear facet of the hypocone), a somewhat reduced m3 relative to m2, a premolariform ?P3 or ?P4 lacking a metacone, and a relatively large hypocone on upper molars. These characters reinstate Valentinella as a valid genus. We also describe Mistralestes arcensis gen. etsp. nov. from a newly discovered locality (La Cairanne‐Highway, south‐eastern France, late Campanian). Mistralestes is defined by a robust premolariform p5 with no cingulid, paraconid, or metaconid; molars with a transverse protocristid, a gradual compression of the trigonid from m1 to m3, and paracristid and protocristid probably confluent on m3. Based on comparisons and phylogenetic analyses, Valentinella and Mistralestes may belong to Zhelestidae but this systematic attribution remains poorly supported. © 2013 The Linnean Society of London